Relationship between quality of work-life, resilience and burnout among nursing professionals during COVID-19 pandemic in Iran: A cross-sectional study - Zahednezhad, Hosein; Zareiyan, Armin; Zargar Balaye Jame, Sanaz (Belitung Nursing Journal, 2021)
Background: The COVID-19 pandemic and the increased workload and stress associated with the disease prevalence have posed a high risk of burnout to nurses. The effects of the workplace and environmental factors on resilience and burnout among nursing professionals have not been investigated in Iran. Objective: Present study aimed to assess a model linking quality of work-life to the resilience and various dimensions of burnout among Iranian nursing professionals based on the health service workplace environmental resilience model. Methods: This was a cross-sectional study performed on 202 Iranian nurses employed in three educational hospitals. Maslach burnout inventory, Brooks’ quality of nursing work-life survey, and an abbreviated version of the Connor-Davidson resilience scale were used to collect data. The correlation between the study variables was assessed by conducting path analysis in AMOS 22. Results: The final model demonstrated adequate fit. The quality of working life indirectly affected burnout via a direct impact on nursing professionals’ resilience (p <0.001, β = 0.39). In addition, resilience had negative, significant effects on all the dimensions of job burnout. The quality of work-life also had negative and significant effects on emotional exhaustion (p <0.001, β = -0.38) and reduced personal accomplishment (p <0.001, β = - 0.38). Conclusion: Resilience and quality of work-life are protective variables against burnout in nursing professionals. Nursing managers can increase resilience and decrease burnout among nursing professionals by adopting policies that can improve the quality of work life.